Direct Democracy in Europe Developments and Prospects - Pállinger, Zoltán Tibor.; Pállinger, Zoltán Tibor.; Kaufmann, Bruno.; Kaufmann, Bruno.; Marxer, Wilfried.; Marxer, Wilfried.; Schiller, Theo.; Schiller, Theo. (Direct Democracy in Modern Europe, 2007)
Modern direct democracy has recently become an essential element of political life in many countries in Europe - and worldwide. The initiative and referendum process offers extra channels of participation and can serve as an important supplementary institution in representative democratic systems. This first volume of the new series Direct Democracy in Modern Europe features sixteen systematic and broadly empirical approaches to the study of modern direct democracy within the context of European politics including - system contexts and effects of the initiative and referendum process - theoretical approaches and basic values in modern direct democracy - the quality and institutional design of direct democratic mechanisms - aspects of information and communication - institutional performance and economic effectiveness - transnational challenges and the development of direct democracy in Europe.